2018
DOI: 10.1038/s41598-018-33545-1
|View full text |Cite
|
Sign up to set email alerts
|

Showcasing the role of seawater in bacteria recruitment and microbiome stability in sponges

Abstract: We studied the core bacterial communities of 19 sponge species from Nha Trang Bay (Central Vietnam), with particular emphasis on the contribution of planktonic seawater bacteria to the sponge core microbiomes. To ensure consistent sponge-microbe associations and accurate identification of planktonic bacteria transmitted from seawater, we were very restrictive with the definition of the sponge core microbiomes (present in all the replicates), and with the identification of valid biological 16S rRNA gene sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 58 publications
7
59
2
2
Order By: Relevance
“…Therefore, our results show that while genotype exerts an effect on non‐core microbiome taxa, it does not drive abundances of core taxa. This lends support to the theory that horizontal transmission has an important role in forming the core microbiome (Turon et al, ), as we may expect vertical transmission to produce significant genotype–core microbiome relationships. However, some refinement of the core microbiome concept and, in particular, the associated methodologies to define and identify ‘core’ taxa may be required to further our understanding of their significance, role and transmission.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Therefore, our results show that while genotype exerts an effect on non‐core microbiome taxa, it does not drive abundances of core taxa. This lends support to the theory that horizontal transmission has an important role in forming the core microbiome (Turon et al, ), as we may expect vertical transmission to produce significant genotype–core microbiome relationships. However, some refinement of the core microbiome concept and, in particular, the associated methodologies to define and identify ‘core’ taxa may be required to further our understanding of their significance, role and transmission.…”
Section: Discussionsupporting
confidence: 78%
“…At the 99% OTU level, the core microbiome in our study was comprised of two OTUs, which made up 1.2% and 1.3% of the total microbiome in Long Key and Kemp Channel, respectively. This core community appears small compared with results reported in some previous studies on sponges (Marino et al, ; Turon et al, ). Marino et al () found 119 core OTUs among 18 I. campana individuals, comprising 79.2%–87.0% of the total microbiome.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations